Cosmological implications of the composite spectra of galactic X-ray binaries constructed using MAXI data. Issue 2 (27th May 2019) - Islam, Nazma; Ghara, Raghunath; Paul, Biswajit; Choudhury, T Roy; Nath, Biman B
Abstract: We have investigated the long-term average spectral properties of galactic X-ray binaries in the energy range of 3–20 keV, using long-term monitoring data from MAXI –Gas Slit Camera (GSC). These long-term average spectra are used to construct separately the composite spectra of galactic high mass X-ray binaries (HMXBs) and low mass X-ray binaries (LMXBs). These composite spectra can be described empirically with piece-wise power law with three components. X-rays from HMXBs are considered as important contributors to heating and ionization of neutral hydrogen in the intergalactic medium during the Epoch of Reionization. Using the above empirical form of the composite HMXB spectra extrapolated to lower energies as an input, we have studied the impact of these sources on the 21-cm signal using the outputs of N -body simulation and 1D radiative transfer. The heating due to the composite spectrum is less patchy compared to power-law spectrum with a spectral index α = 1.5, used in previous studies. The amplitude of the heating peak of large-scale power spectrum, when plotted as a function of the redshift, is less for the composite spectrum.